Implementation Of Local Goverment Policies In The Utilization Of Groundwater For Business Activities - Arief Prayitno; Endang Sutrisno; Alip Rahman; Bella Carla (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Excessive use of groundwater depletes reserves ofgroundwater resources in a short period of time,resulting in various impacts. This study discussespolicies regarding the use of groundwater in CirebonRegency and the government's efforts to overcomethreats due to groundwater exploitation. The researchmethod used is empirical juridical. Arrangementsregarding the legal basis for the use, extraction andprotection of groundwater are regulated in LawNumber 11 of 1974 concerning Irrigation, Minister ofEnergy and Mineral Resources Regulation Number20 of 2017 concerning Guidelines for DeterminingGroundwater Acquisition Value West Java GovernorRegulation Number 97 of 2020 concerningImplementation Regulations of West Java ProvinceRegional Regulation Number 1 of 2017 concerningGroundwater Management West Java ProvincialRegulation Number 1 of 2017 2017 concerningGroundwater Management so that the continuity ofgroundwater availability is maintained, this becomesthe legal basis for regional stakeholders. The CirebonRegency government's policy in tackling groundwaterexploitation must be based on applicable legalprovisions. In its application in Cirebon Regency,research found that there are companies that carry outbusiness activities by exploiting excessivegroundwater